Routledge handbook of tennis
1 online resource.
Keywords: "Tennis is one of the world's most popular sports, as levels of participation and spectatorship demonstrate. Moreover, tennis has always been one of the world's most significant sports, expressing crucial fractures of social class, gender, sexuality, race and ethnicity - both on and off court. This is the first book to undertake a survey of the historical and socio-cultural sweep of tennis, exploring key themes from governance, development and social inclusion to national identity and the role of the media. It is presented in three parts: historical developments; culture and representations; and politics and social issues, and features contributions by leading tennis scholars from North America, Europe, Asia and Australia. The most authoritative book published to date on the history, culture and politics of tennis, this is an essential reference for any course or program examining the history, sociology, politics or culture of sport"--